S113. TELE-PSYCHIATRIC AFTER CARE (TAC) CLINIC FROM INDIA: PATTERN OF CONTINUITY OF CARE OF PATIENTS WITH SEVERE MENTAL DISORDERS. (18th May 2020) - Nagendrappa, Sachin; Reddy Mukku, Shivashanker; Venu, M A; Harshitha, Nisha R; Manjunatha, Narayana; Sivakumar, P T; Naveen Kumar, Channaveerachari; Bada Math, Suresh
Abstract: Background: In India, follow up rates of persons with severe mental disorders are as low as 30%, necessitating the development of alternative models to ensure continuity of care (COC). Telepsychiatry is one such promising avenues that use audio-visual communication to provide effective services at affordable cost and convenience. A pilot study from the telepsychiatry aftercare (TAC) clinic has shown promising results in terms of acceptability, feasibility, clinical effectiveness and cost-saving benefits. This study aimed at evaluating the pattern of services of TAC clinic for patients with severe mental disorders Methods: This study was conducted at TAC Clinic, Tele Medicine Centre of National Institute of Mental health and Neurosciences, Bengaluru. This study was approved by the institute's ethics committee. TAC is a psychiatrist-based clinic for follow-up in a videoconference mode for patients who are stable and unlikely to have psychiatric /medical emergencies. Chart review was done for all patients who availed services of TAC clinic between October 2016 to September 2019 Results: We reviewed charts of 90 patients. Primary psychiatric diagnosis were: Schizophrenia 34 (17 males, 17 females), bipolar disorder in 35 (23 males, 12 females), Psychosis NOS 21 (6 males, 15 females). The mean age was 38.84± (16.28) years; 82% of patients belonged to the middle socioeconomic status and 65.1% were from an urban background. 242 TAC appointments were given during the study period. Among them, 9 got canceled (7 technical reasons, 2 non-availability of the patient), and 2 were aborted due to active suicidal tendencies. A total of 231 TAC consultations successfully completed i.e sessions were conducted successfully. Among these 85.29% sessions were successful in schizophrenia, 94.28% in BPAD, and 95.23 % psychosis NOS. Minimum of 1 to 3 consultations were done in 67.77% of the patients, 13.33% had between 4–6 consultations and 18.7% had more than 7 consultations. The average duration of each session was 18.33 (±6.40) minutes. The total mean duration for all consultation for each patient was 101.40 (±160.61) minutes. Patients avoided an average of 1702.18(±1900) KM one-sided travel. In terms of psychopathology, 94.4% of patients with Schizophrenia, 81.71% with BPAD and 95.23%with psychosis NOS showed good improvement in their clinical condition. Common reasons for choosing TAC were: long-distance 51(48.1%), the convenience of using technology 21(19.8%), and cost of care 18(17%). Discussion: Logistic issues were of significant concern among the patients and the families in our study, the high success rate and good improvement during TAC depict high acceptability and feasibility. There are a felt need and demand to provide continuous specialist services bypassing all the logistic barriers. The TAC service in our facility is one such method that has started to ensure the continuity of care for patients with severe mental illness.